1997
DOI: 10.1007/s004220050398
|View full text |Cite
|
Sign up to set email alerts
|

Does the brain use sliding variables for the control of movements?

Abstract: Delays in the transmission of sensory and motor information prevent errors from being instantaneously available to the central nervous system (CNS) and can reduce the stability of a closed-loop control strategy. On the other hand, the use of a pure feedforward control (inverse dynamics) requires a perfect knowledge of the dynamic behavior of the body and of manipulated objects. Sensory feedback is essential both to accommodate unexpected errors and events and to compensate for uncertainties about the dynamics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 34 publications
4
56
0
Order By: Relevance
“…Intermittency is characterised by sub-movements which are triggered by an error crossing a threshold (Asai et al 2009;Hanneton et al 1997;Miall et al 1993;Wolpert et al 1992). In both self-selected and fast speed conditions, the weak correlations observed between the peak velocity and the constant error suggested that the young adults used adjustments to reach the endpoint position (Messier and Kalaska 1999).…”
Section: Continuous Vs Intermittent Modelsmentioning
confidence: 99%
“…Intermittency is characterised by sub-movements which are triggered by an error crossing a threshold (Asai et al 2009;Hanneton et al 1997;Miall et al 1993;Wolpert et al 1992). In both self-selected and fast speed conditions, the weak correlations observed between the peak velocity and the constant error suggested that the young adults used adjustments to reach the endpoint position (Messier and Kalaska 1999).…”
Section: Continuous Vs Intermittent Modelsmentioning
confidence: 99%
“…Nevertheless, the two algorithms use different adaptation laws: adaptive sliding control uses the sliding variable, whereas feedback error learning uses a neural network controller. Hanneton et al (Hanneton, Berthoz et al 1997) proposed that the experimental data of human control of movement are consistent with the predictions of adaptive sliding control.…”
Section: Feedback Error Learning As Adaptive Sliding Controlmentioning
confidence: 79%
“…The rationale for intermittent control is that it confers online flexibility and adaptability. This rationale has caused many investigators to consider whether intermittent control is an appropriate paradigm for understanding biological motor control (Craik, 1947a,b;Vince, 1948;Bekey, 1962;Navas and Stark, 1968;Neilson et al, 1988;Miall et al, 1993a;Hanneton, Berthoz, Droulez, and Slotine, 1997;Neilson and Neilson, 2005;Loram and Lakie, 2002).…”
Section: Identification Of Intermittent Control: Detecting Intermittencymentioning
confidence: 99%
“…The existence of discontinuities within the control signal has been interpreted as submovements or serially planned control sequences (Navas and Stark, 1968;Poulton, 1974;Miall et al, 1993a;Miall, Weir, and Stein, 1986;Hanneton et al, 1997;Loram and Lakie, 2002), 2. Constancy in the modal rate of discontinuities, typically around 2-3 per second, has been interpreted as evidence for a central process with a well defined timescale (Navas and Stark, 1968;Poulton, 1974;.…”
Section: Intermittent Control In Man and Machine Peter Gawthrop Henrmentioning
confidence: 99%